PENGEMBANGAN MODEL BAHAN BELAJAR MANDIRI BERBASIS ANDRAGOGI UNTUK MENINGKATKAN KOMPETENSI PENDIDIK ANAK USIA DINI - Hulukati, Wenny (JIV-Jurnal Ilmiah Visi, 2011)
This research aims at creating a model of self- learning materials to improve PAUD teacher’s competence in facilitating and developing learning in early childhood education. The model to be developed based on andragogy approach consists of the learning and teaching materials, learning and teaching guidelines, and assessment and evaluation guidelines. To reach the research objectives. research and development method was employed. The data was collected through observation, interview, questionnaire, and test. Data analysis used qualitative analysis capturing the analysis of preliminary research data, the result of expert validation, and try out data. Quantitative analysis was also integrated in this study for the experiment data. The result of this study shows that the self learning materials developed in this research can improve the early childhood education teacher’s competence in teaching and learning process. It is recommended therefore to use this andragogy principles based model of self learning package for early childhood education teachers.